2011
DOI: 10.4066/amj.2011.559
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fine needle aspiration cytology and histopathology in diagnosing cervical lymphadenopathies

Abstract: FNAC can distinguish tubercular lymphadenitis from reactive and granulomatous lymphadenitis in majority of cases. Similarly, it can distinguish well between benign and malignant lymphadenopathies. It can be used as an initial investigation for routine screening of cervical lymphadenopathies where facilities of histopathology are not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 9 publications
7
13
0
Order By: Relevance
“…Most common lesion on cytology was found to be reactive hyperplasia 530 cases (55.2%). The result was comparable to study done by Mohanty et al (2) , Kochhar K et al (3) and Adhikari P et al (4) wherein reactive lymphadenopathy was the most common lesion found. Whereas Khajuria R et al (5) did the same study at our institution in 2006 and found tuberculous lymphadenitis to be the most common.…”
Section: Resultssupporting
confidence: 81%
“…Most common lesion on cytology was found to be reactive hyperplasia 530 cases (55.2%). The result was comparable to study done by Mohanty et al (2) , Kochhar K et al (3) and Adhikari P et al (4) wherein reactive lymphadenopathy was the most common lesion found. Whereas Khajuria R et al (5) did the same study at our institution in 2006 and found tuberculous lymphadenitis to be the most common.…”
Section: Resultssupporting
confidence: 81%
“…Also cervical group are most common to be involved by metastasis 675/1324 (51%) cases and the primary was most often from the oral cavity, which was similar to other studies 3,5,15 with Squamous Cell Carcinoma being the most common histological type. 9,10,15,16 Rates for carcinoma of oral cavity, pharynx, esophagus and male larynx are highes t in India, probably due to the use of multiple tobacco products.…”
Section: 2345supporting
confidence: 73%
“…The incidence of granulomatous inflammation was observed to vary from 9.2% to 25.45% in other studied. 1,2,5 Tuberculous lymphadenopathy diagnosed by cytology alone occurred in 260/1774 (14.65%) of our cases. Other previous studies showed this condition varying from 7.8% to 52%.…”
Section: 2345mentioning
confidence: 99%
“…FNAC is a simple, safe, rapid, accurate, minimally invasive and relatively pain free procedure which is of particular relevance in cervical lymphadenopathy because of easy accessibility of target sites and thus excellent patient compliance [2,6]. Since this technique lends itself to out-patient diagnosis, it is eminently suited for use in peripheral medical centers and places where facilities for histopathology are not available [7].…”
Section: Discussionmentioning
confidence: 99%
“…In our study also, reactive lymphadenitis (39.4%) was the most common cytological diagnosis, however, metastasis (38.2%) was found to be much more common than tuberculosis (11.5%). Other studies from Pakistan, [3,15] Nepal [7] and India [16] reported tubercular lymphadenitis as the most common cause of cervical lymphadenopathy. In contrast, metastasis was the most common cytological diagnosis in some other studies [17,18].…”
Section: Fnac Diagnosismentioning
confidence: 99%